FLARE STARS AND CLOUDS OF INTERSTELLAR MATTER - HARO, G (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1955)
The flare stars found in the Orion Nebula and the flare variables discovered in the solar vicinity have similar characteristics: late-type stars, rapid and irregular light variations, emission lines in their quiescent spectra, similar spectra to T-Tauri s
BOL OBS TONAN TACUB
Keywords: FLARE STARS, CLOUDS, INTERSTELLAR, MATTER; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS